2020
DOI: 10.21203/rs.2.20391/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validity and Item Response Theory Properties of the Patient Health Questionnaire-9 for Primary Care Depression Screening in Mozambique (PHQ-9-MZ)

Abstract: Background: Depression is one of the leading causes of disability in Mozambique; however, few patients with depression are identified in primary care. To our knowledge, there are no validated tools for depression screening in Mozambique. The aim of this study was to validate the Patient Health Questionnaire-9 (PHQ-9) for use in primary care settings in Mozambique. Methods: The PHQ-9 was adapted using a structured multi-phase process led by a team of bilingual experts followed by a review by lay individuals and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…α = 0 864 observed for our isiXhosa PHQ-9 is compatible with previous reports of Cronbach's α of 0.76 (South Africa (Bhana et al, 2015)), 0.78 (Kenya (Monahan et al, 2009)), and 0.83 (Tanzania (Fawzi et al, 2019)) for the PHQ-9 in other African contexts. Similarly, the factor structure of our isiXhosa PHQ-9 was comparable with other versions in African nations (Kenya (Monahan et al, 2009) and Mozambique (Cumbe et al, 2020)). Overall, we have shown that our isiXhosa PHQ-9 performs comparably to other versions, which supports the adoption of this translation into research and clinics.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…α = 0 864 observed for our isiXhosa PHQ-9 is compatible with previous reports of Cronbach's α of 0.76 (South Africa (Bhana et al, 2015)), 0.78 (Kenya (Monahan et al, 2009)), and 0.83 (Tanzania (Fawzi et al, 2019)) for the PHQ-9 in other African contexts. Similarly, the factor structure of our isiXhosa PHQ-9 was comparable with other versions in African nations (Kenya (Monahan et al, 2009) and Mozambique (Cumbe et al, 2020)). Overall, we have shown that our isiXhosa PHQ-9 performs comparably to other versions, which supports the adoption of this translation into research and clinics.…”
Section: Discussionsupporting
confidence: 67%
“…To demonstrate the comparability of our isiXhosa-language PHQ-9 with other versions of the PHQ-9, in addition to describing the inherent psychometric properties of our translation, we also present comparisons with published psychometric properties of other PHQ-9 versions in African and global contexts. These include a seTswana version in South Africa (Bhana et al, 2015), an English version in Kenya (Monahan et al, 2009), a Portuguese version in Mozambique (Cumbe et al, 2020), a Swahili version in Tanzania (Fawzi et al, 2019), and a recent multi-country, multi-language validation study (Bianchi et al, 2022).…”
Section: Exploratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation